Quantifying Ship Strike Risk to Breeding Whales in a Multiple-Use Marine Park: The Great Barrier Reef - Smith, Joshua N.; Kelly, Natalie; Childerhouse, Simon; Redfern, Jessica V.; Moore, Thomas J.; Peel, David (Frontiers in Marine Science, 2020)
Spatial risk assessments are an effective management tool used in multiple-use marine parks to balance the needs for conservation of natural properties and to provide for varying socio-economic demands for development. The multiple-use Great Barrier Reef Marine Park (GBRMP) has recently experienced substantial increases in current and proposed port expansions and subsequent shipping. Globally, large whale populations are recovering from commercial whaling and ship strike is a significant threat to some populations and a potential welfare issue for others. Within the GBRMP there is spatial conflict between the main breeding ground of the east Australian humpback whale population which overlaps the main inner shipping route that services several large natural resource export ports. The east coast humpback whale population is one of the largest humpback whale populations globally, exponentially increasing (11% per annum) close to the maximum potential rate and estimated to reach pre-exploitation population numbers in the next 4-5 years. We quantify the relative risk of ship strike to calving and mating humpback whales, with areas of highest relative risk coinciding with areas offshore of two major natural resource export ports. We found females with a dependent calf had a higher risk of ship strike compared to groups without a calf and their inshore movement and coastal dependence later in the breeding season increases their overlap with shipping although their lower relative abundance decreases risk. The formalisation of a two-way shipping route has provided little change to risk and projected risk estimates indicate a three- to five-fold increase in risk to humpback whales from ship strike over the next ten years. Currently, the whale Protection Area in the GBRMP does not cover the main mating and calving areas, whereas provisions within the legislation for establishment of a Special Management Area during the peak breeding season in high risk areas could occur. A common mitigation strategy of re-routing shipping lanes to reduce risk is not a viable option for the GBRMP due to physical spatial limitations imposed by the reef, whereas speed restrictions could be the most feasible based on current ship speeds if mitigation were deemed necessary.